Música no neoxamanismo de ayahuasca: as cerimônias da Sétima Lua e do Voo da Águia - Weik, Christian Alberto (2017)
This study focuses on music in neoxamanic ceremonies with ayahuasca, a tea made from two plants from Amazonia. Ritually used, the infusion produces amplified states of consciousness, expressed through the mirações. In this context, music plays a fundamental role in the configuration of ritual as well as in the perceptions and contents of consciousness. This dissertation presents, discusses, and analyzes the central role of music and its ways of insertion in two neoxamanic ceremonies performed in Camaragibe, metropolitan region of Recife, Brazil. Based on a bibliographical research that contemplated the diverse traditional uses of the beverage, as well as its musical repertoires, it was defined a theoretical framework compatible with the amplitude of the theme. The methodological support of this study is an ethnographical research focused on field experience in the neoxamanic ceremonies: the Sétima Lua (Seventh Moon), conducted by the shaman Rosemberg Silva, and the Voo da Águia (Flight of the Eagle), conducted by the shamans Leo Artese and Fany Carolina. The neoxamanic movement has proved to be the cradle of an entheogenic circuit, aligned with a new religious consciousness, eclectic and hybrid. In this ritual, the ayahuasca, as a central medicinal plant of the forest, is used together with other secondary medicinal plants, such as tobacco, sananga and rape. Each one of them has its own repertoire of rites, symbols and songs, in a constant process of dialogue, expansion and transformation. In this context, music has several functions, such as: to call and to direct the força (force) of ayahuasca; to transmit cosmological statements; to eliminate the symptoms of the peia; to articulate synaesthetic knowledge, also expressed in the reception of new songs of ayahuasca; among others aspects.